Robots for Foreign Language Learning: Speaking Style Influences Student Performance - Fischer, Kerstin; Niebuhr, Oliver; Alm, Maria (Frontiers in Robotics and AI, 2021)
Much previous research suggests that teachers' individual characteristics may affect students' performance; however, which factors are particularly helpful is as yet unclear and methodologically very difficult to assess. In this paper, we study the effects of robots' speaking styles when instructing students on a task. 40 participants saw a brief video in which a robot presented its instructions either in a charismatic or a not so charismatic speaking style. Participants' task was then to produce foreign language sentences on the basis of visualizations of the prosodic properties of these sentences. A subsequent analysis of participants' productions shows that language learners' performance was significantly better when the robot had delivered its instructions in a charismatic voice. The results suggest not only that a charismatic speaking style may be crucial for teachers in general and hence one of the factors causing the interpersonal variation between teachers, but also that students can benefit from instructions by robots delivered in a charismatic speaking style.